Will use of patient portals help to educate and communicate with patients with diabetes?. Issue 5 (May 2018) - Jackson, Sara L.; DesRoches, Catherine M.; Frosch, Dominick L.; Peacock, Sue; Oster, Natalia V.; Elmore, Joann G.
Highlights: Managing a chronic illness such as diabetes can be overwhelming for patients. Having access to their patient portal may help patients with education and their self-care. Patients with and without diabetes had positive perceptions of the patient portal. Patients with diabetes perceived an even greater benefit than those without. Patient portals are an important tool to help patients with chronic diseases. Abstract: Objective: Chronic disease management can require daily attention, and increased levels of patient activation and engagement. We examined whether patients with diabetes perceive a greater benefit to having electronic access to their doctors' clinic notes compared to patients without diabetes. We hypothesized that easy electronic access to these notes may help patients with self-care by improving education and communication. Methods: Survey of patients with and without diabetes in Massachusetts and Pennsylvania about perceptions of potential benefits and risks of reading their visit notes via an electronic patient information portal. Administrative data were used to identify patients with diabetes; we compared their perceptions to those of patients without diabetes. Results: The majority of patients (both with and without diabetes) perceived a positive impact of using the portal. Patients with diabetes were significantly more likely to believe that having access to and reading their notes would help them take their medication better and take better care of themselves. Conclusions: Patients with chronic diseases such as diabetes might receive an even greater benefit from access to their doctors' notes than the general patient population. Practice implications: Doctors should encourage their patients with diabetes (or other chronic diseases) to use patient portals.